Periguetes, sapatões e mulherzinhas: (des) construindo o que é “ser mulher” no campo de futebol - Oliveira, Valleria Araujo de (2014)
The scope of this study is a social research and presents itself as ethnography. This research investigates how gender identities of the female soccer players who practice this sport as leisure in two spaces in the city of Goiânia, Goiás are experienced and perceived in these locations. As an instrument for data collection it was used the observations of participants as well as the implementation of socio-economic questionnaires and semi-structured interviews. The analysis and description of the data enabled us to understand how gender identifications of these women are perceived and how these female players act in spaces/places socially elected by common sense as predominantly male, specifically the soccer field.